Пространственная характеристика свода черепа у людей с различными типами строения головы = Volume characteristics of the cranial vault in people with different types of structure of the head = Просторова характеристика склепіння черепа у людей з різними типами будови голови - Vovk, O. Y.; Sukhonosov, R. A. (Journal of Education, Health and Sport, 2016)
Vovk O. Y., Sukhonosov R. A. Пространственная характеристика свода черепа у людей с различными типами строения головы = Volume characteristics of the cranial vault in people with different types of structure of the head = Просторова характеристика склепіння черепа у людей з різними типами будови голови Journal of Education, Health and Sport. 2016;6(10):430-442. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164186 http://ojs.ukw.edu.pl/index.php/johs/article/view/3970 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК: 611.714.1.068 ПРОСТРАНСТВЕННАЯ ХАРАКТЕРИСТИКА СВОДА ЧЕРЕПА У ЛЮДЕЙ С РАЗЛИЧНЫМИ ТИПАМИ СТРОЕНИЯ ГОЛОВЫ О. Ю. Вовк, Р. А. Сухоносов Харьковский национальный медицинский университет Кафедра анатомии человека 61022, г. Харьков, пр. Науки, 4 (тел.+38-050-475-09-15, vovkoleg80@ukr.net). Реферат Цель – установить пространственную характеристику крайних форм строения свода черепа с помощью стереотопометрических методик. Методы – краниометрия черепа; стереотопометрия черепа; вычисления краниологических индексов; вариационно-статистический анализ полученных результатов. В ходе исследования выявлено три типа строения черепа, при этом, в сагиттальной координатной плоскости (oy) имеются различные типы конфигурации формы свода черепа. У брахикранов отмечаются расширенно-укороченные типы строения; у мезокранов – усредненные; у долихокранов – суженно-удлинённые. В горизонтальной плоскости (ох) установлено, что при брахикрании выявляются расширенно-округленные формы, у представителей с мезокранным типом строения свода черепа обычно имеется усредненные формы, долихокранный тип строения свода черепа характеризуется появлением суженно-удлинённой формы. В фронтальной плоскости (oz) для брахикранов характерно расширенно-овоидные формы, у мезокранов преобладают усредненно-овоидные, у долихокранов отмечаются суженно-овоидные формы свода черепа. Ключевые слова: свод черепа, индивидуальная анатомическая изменчивость, стереотопометрия, морфометрия, краниометрия. VOLUME CHARACTERISTICS OF THE CRANIAL VAULT IN PEOPLE WITH DIFFERENT TYPES OF STRUCTURE OF THE HEAD O. Y. Vovk, R. A. Sukhonosov Kharkiv National Medical University Department of Human Anatomy Abstract Objective. Establish the volume characteristics of terminal forms of calvarial structure using stereotopometric techniques. Methods: craniometry of skull; stereotopometry of skull; calculating of the cranial index; variation-statistical analysis of the results. Results. The study had revealed three types of structure of the skull, thus, in the sagittal reference plane (oy) are different types of configuration forms calvarium. In brachicranial humans we have seen increasing extended-shortened types of buildings; in mezocranial – average; in dolichocranial – narrowing-elongated. In the horizontal plane (ox) in brachicranial type identified extendedly-rounded shape, with the representatives of the cranial vault mezocranial type structure usually has averaged shape, dolichocranial type of cranial vault structure is characterized by the appearance of the narrowing-elongated shape. In the frontal plane (oz) for brachicranial characteristic extendedly-ovoid shape, in mezocranial have dominated averaged-ovoid, at dolichocranial marked narrowing-ovoid shape of the cranial vault. Keywords: cranial vault, individual anatomical variability, stereotopometry, morphometry, craniometry.